2006
DOI: 10.1007/s00421-006-0269-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hsp72 and norepinephrine in the moderate exercise-induced stimulation of neutrophils’ microbicide capacity

Abstract: The influence of a single session of moderate exercise (45 min at 55% of VO(2 )max) performed by young sedentary men (23-25 years old) on the microbicidal capacity of neutrophils was compared by using both direct (killing of phagocytosed Candida albicans) and indirect (superoxide anion production measured by NBT reduction) techniques. In addition, the role of norepinephrine and heat shock protein (Hsp) 72 in the modulation of microbicide capacity of neutrophils was evaluated during the protocol of exercise and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 31 publications
(28 reference statements)
1
25
0
Order By: Relevance
“…Whitham et al (2006) demonstrated increased eHsp72 was associated with higher plasma levels of catecholamines and heart rate, whilst it has also been observed that following passive heating, neither epinephrine nor norepinephrine was solely responsible for eHsp72 release (Whitham et al 2007). Johnson and Fleshner (2006) identified α-adrenergic stimulation, notably through norepinephrine elevation (Nielsen et al 1997;Ortega et al 2006;Whitham et al 2006;Giraldo et al 2010;Iguchi et al 2012) as responsible for Hsp72 release into the circulation, this alongside the work of Whitham et al (2006Whitham et al ( , 2007 suggest a requirement for individuals to be presented with sustained physiological challenge during exercise-heat stress (Johnson and Fleshner 2006). Exercise intensity, or α-adrenergic stimulation via norepinephrine is likely required to be above an intensity threshold to elicit significant eHsp72 response with the greater exercise intensity data from Périard et al (2012) leading to data contrasting that of Marshall et al (2006).…”
Section: Discussionmentioning
confidence: 98%
“…Whitham et al (2006) demonstrated increased eHsp72 was associated with higher plasma levels of catecholamines and heart rate, whilst it has also been observed that following passive heating, neither epinephrine nor norepinephrine was solely responsible for eHsp72 release (Whitham et al 2007). Johnson and Fleshner (2006) identified α-adrenergic stimulation, notably through norepinephrine elevation (Nielsen et al 1997;Ortega et al 2006;Whitham et al 2006;Giraldo et al 2010;Iguchi et al 2012) as responsible for Hsp72 release into the circulation, this alongside the work of Whitham et al (2006Whitham et al ( , 2007 suggest a requirement for individuals to be presented with sustained physiological challenge during exercise-heat stress (Johnson and Fleshner 2006). Exercise intensity, or α-adrenergic stimulation via norepinephrine is likely required to be above an intensity threshold to elicit significant eHsp72 response with the greater exercise intensity data from Périard et al (2012) leading to data contrasting that of Marshall et al (2006).…”
Section: Discussionmentioning
confidence: 98%
“…FM patients are more prone to C. albicans infections than HW [39], which seems consistent with the increased phagocytic and microbicidal capacities against C. albicans found in the neutrophils from our FM patients. This greater phagocytic and fungicidal capacity (together with a greater chemotactic capacity) of neutrophils could be mediated by the raised circulating concentration of NA and eHsp72 in the FM patients, since it has been reported that increased systemic levels of NA and eHsp72 mediate the stimulation of chemotaxis, phagocytosis and the fungicidal activities of neutrophils [22,40,41,42]. However, the FM group’s decreased latex bead phagocytic capacity (a less specific form of phagocytosis because it is not mediated by pre-opsonization through antibodies) is suggestive of an immunosuppression mediated by the less specific innate immune response carried out by neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies on sedentary young men performed in our laboratory based on (1) the direct effect of exercise, (2) evaluation of plasma concentrations of stress hormones and (3) in vitro incubation of neutrophils with the physiological concentrations of these hormones in a basal situation versus the raised levels after exercise, it was concluded that the moderate exercise-induced stimulation of neutrophil phagocytosis is mediated by NA, with the participation of both ␣ -and ␤ -adrenergic receptors [29] . However, although physiological concentrations of NA also stimulated the neutrophil microbicide capacity through both ␣ -and ␤ -receptors, it did not mediate the increased killing of Candida albicans during exercise, this effect being mediated by Hsp72 [30] . The same results for phagocytosis and microbicide capacity after moderate exercise (45 min at 55% VO 2 max on an ergonometric bicycle) were also found in sedentary young women (data not shown).…”
Section: Catecholamines As Neuroendocrine Mediator In the Modulation mentioning
confidence: 99%